Assessment of maximal aerobic velocity in soccer players by means of an adapted Probst field test - Labsy, Z.; Collomp, K.; Frey, A.; de Ceaurriz, J. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The aim of the study was to test the accuracy of 2 versions of a specific soccer field test for assessing maximal aerobic velocity (MAV) in soccer players. The original Probst field test consists of repetitions of 280 m runs including changes in direction separated by a 30-second rest with an initial speed of 8.4 km x h(-1) and a 0.6 km x h(-1) increment at each stage. The adapted version was carried out with the same protocol but constant stages of 2-minute durations and a 1.2 km x h(-1) increment at each stage. METHODS: Trained soccer players completed 4 outdoor field tests: the original and adapted field Probst tests, both with and without changes in direction, in order to determine the velocities at exhaustion. They all underwent at the same time 3 laboratory tests in order to determine MAV during a classical graded treadmill test, a laboratory test with the same stages as the original Probst test and the adapted Probst test. RESULTS: The velocities at exhaustion with and without changes in direction obtained during the adapted Probst field test, and the MAV obtained in the laboratory were highly correlated. All were significantly lower than the velocities at exhaustion obtained during the original version. CONCLUSIONS: The adapted version was a better predictor of MAV in trained soccer players than was the original test.